2018
DOI: 10.1038/s41598-018-23891-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis inhibition by hibernating bear serum leads to increased protein content in human muscle cells

Abstract: Muscle atrophy is one of the main characteristics of human ageing and physical inactivity, with resulting adverse health outcomes. To date, there are still no efficient therapeutic strategies for its prevention and/or treatment. However, during hibernation, bears exhibit a unique ability for preserving muscle in conditions where muscle atrophy would be expected in humans. Therefore, our objective was to determine whether there are components of bear serum which can control protein balance in human muscles. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Different studies have reported very different trends regarding the seasonal variations of plasma proteins and amino acids (Table 1). Despite not consuming any protein during the fasting that accompanies hibernation, the protein content of serum decreases little during this period (4%-17%; Chanon et al, 2018) and increases in the case of some proteins and amino acids (Table 1). Hellgren (1998) even suggested that increases in protein metabolism could (a) prevent its catabolism into carbon dioxide, water, and urea and (b) supply the needs of specific enzymes such as lipolytics, gluconeogenic, or proteolytic.…”
Section: Metabolism Of Nitrogenous Substances and Turnover Of Protementioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have reported very different trends regarding the seasonal variations of plasma proteins and amino acids (Table 1). Despite not consuming any protein during the fasting that accompanies hibernation, the protein content of serum decreases little during this period (4%-17%; Chanon et al, 2018) and increases in the case of some proteins and amino acids (Table 1). Hellgren (1998) even suggested that increases in protein metabolism could (a) prevent its catabolism into carbon dioxide, water, and urea and (b) supply the needs of specific enzymes such as lipolytics, gluconeogenic, or proteolytic.…”
Section: Metabolism Of Nitrogenous Substances and Turnover Of Protementioning
confidence: 99%
“…During hibernation brown bears experience shivering , with periods that can exceed an hour in duration where activations lasting less than 0.2 s and occur every 3-10 s. Shivering may stimulate skeletal muscles enough to maintain muscular fitness (captive brown bears, Lin, Hershey, Mattoon, & Robbins, 2012). It has also been suggested that the plasma of hibernating bears has antiproteolytic properties, thus inhibiting muscle loss (Chanon et al, 2018;Fuster, Busquets, Almendro, López-Soriano, & Argilés, 2007;Salmov et al, 2015) and that constant levels of prostaglandins in muscle could contribute to muscle sparing in bears (Giroud et al, 2018).…”
Section: Skeletal Response To Hibernation Bone Turnover and Changementioning
confidence: 99%
“…As described previously [10,77], blood, subcutaneous adipose tissue, and muscle tissue (vastus lateralis) samples were collected at two time points, in February during winter hibernation (W) and in June during summer-active period (S). Blood samples were collected from the jugular vein into 8 ml dry tubes for serum (Vacuette® Z serum Sep Clot Activator, Greiner Bio-One GmbH, Kremsmünster, Austria) or into 10 ml EDTA-coated tubes (BD Vacutainer®, FisherScienti c, Illkirch, France) for plasma.…”
Section: Bear Sample Collectionmentioning
confidence: 99%
“…For all bears, samples were collected at two time points, in February during winter hibernation and in June during summer active period. Blood, subcutaneous adipose tissue, and muscle tissue (vastus lateralis) samples were collected from active (summer) and hibernating (winter) brown bears was performed as described previously [10,59]. Illkirch, France) for plasma.…”
Section: Bear Sample Collectionmentioning
confidence: 99%